Theoretically Predicting Cyberbullying Perpetration in Youth With the BGCM: Unique Challenges and Promising Research Opportunities - Barlett, Christopher P.; Bennardi, Christi; Williams, Sullivan; Zlupko, Talia (Frontiers in Psychology, 2021)
The psychological variables and processes germane to cyberbullying need additional empirical attention – especially for adolescent samples. Myriad studies and meta-analytic reviews have confirmed the deleterious psychological and behavioral consequences of being cyber-victimized. We argue that one method to curtail such effects is to inform interventions aimed at reducing cyberbullying perpetration regarding the why and for whom cyberbullying is likely. This review expands on these issues and emphasizes the Barlett Gentile Cyberbullying Model (BGCM) as the only validated cyberbullying-specific theory to predict cyberbullying perpetration. Our principal thesis is that the wealth of research validating the BGCM has been with adult samples and applying the BGCM to adolescents presents both challenging and exciting research opportunities for future research and intervention development in youth.